2006
DOI: 10.1161/01.atv.0000222152.83069.3f
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Low-Density Lipoprotein Exposure Induces Intercellular Adhesion Molecule-1 and Vascular Cell Adhesion Molecule-1 Correlated With Activator Protein-1 Expression

Abstract: Objective-We tested the hypothesis that direct native low-density lipoprotein (LDL) injection into LDL receptordeficient (LDLR Ϫ/Ϫ ) mice would induce the adhesion molecules intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) in their aortic endothelial cells, and that transcriptional regulation of this pathway involved activator protein-1 (AP-1) but not nuclear factor B (NF-B). Methods and Results-Using tail vein injection of LDL into LDLRϪ/Ϫ mice, we were able to maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
(31 reference statements)
6
22
0
Order By: Relevance
“…101 In vivo administration of native LDL into Ldlr Ϫ/Ϫ -recipient mice induces ICAM-1 as well as VCAM-1 expression. 102 In agreement with in vitro studies, immunohistochemical studies of human vessels indicate that human atherosclerotic plaques contain SMCs that express ICAM-1 in response to IL-1␤. 81 Pretreatment of Apoe Ϫ/Ϫ mice with Abs against ICAM-1 reduced short-term M⌽ homing into atherosclerotic lesions byϷ70%.…”
Section: Icam-1 and ␤ 2 Integrinssupporting
confidence: 70%
“…101 In vivo administration of native LDL into Ldlr Ϫ/Ϫ -recipient mice induces ICAM-1 as well as VCAM-1 expression. 102 In agreement with in vitro studies, immunohistochemical studies of human vessels indicate that human atherosclerotic plaques contain SMCs that express ICAM-1 in response to IL-1␤. 81 Pretreatment of Apoe Ϫ/Ϫ mice with Abs against ICAM-1 reduced short-term M⌽ homing into atherosclerotic lesions byϷ70%.…”
Section: Icam-1 and ␤ 2 Integrinssupporting
confidence: 70%
“…While Statin mediated reduction of VCAM-1 expression is considered to be dependent on the eNOS pathway 43 , this is the first report showing that Ezetimibe is capable of reducing vascular VCAM-1 expression independent of eNOS function. This effect may be related to the reduction of plasma LDL cholesterol in our study, as Verna et al report that LDL can directly induce endothelial adhesion molecule expression by activation of the AP-1 regulatory pathway 44 . Consistent with the Ezetimibe mediated reduction of endothelial activation, mononuclear cell infiltration of the aorta was significantly reduced in apoE ko mice and apoE/eNOS dko mice.…”
Section: Discussionsupporting
confidence: 56%
“…31,36,37 Because these transcription factors have been involved in the regulation of inducible chemokines including CCL20, 34,35 as a first approach we showed that inhibitors of NF-B signaling prevented the upregulation of CCL20 mRNA levels. The involvement of a NF-B site located in the proximal region of CCL20 promoter was demonstrated by serial deletion analysis of promoter-luciferase constructs, site-directed mutagenesis, EMSA, and chromatin immunoprecipitation assays.…”
Section: Discussionmentioning
confidence: 96%